(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2018)
Global awareness is discussed through the experiential learning of six teacher candidates and six teachers on a Fulbright-Hays study abroad program to Israel. The participants focused their learning on four key aspects of global education; multilingual communication – to enhance a world view, historical layering – to understand the peripheries of communities, conflict resolution – an intrinsic component of global citizenship, and geographical interdependence. The participants enhanced their understanding of the multifaceted concepts surrounding globalism, globalization and global education.